2017
DOI: 10.3846/bjrbe.2017.09
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the impact of aging on Gilsonite and Trinidad Epuré modified asphalt binders properties

Abstract: The tests and analyses presented in the paper are related to the 20/30, 35/50 and 50/70 penetration grade road bitumens as well as the asphalt binders obtained through modification of the 35/50 and 50/70 bitumens. The latter were modified by adding to it 3%, 5% and 7% of the Gilsonite natural asphalt and 15%, 25% and 35% of the Trinidad Epuré Z 0/8 natural asphalt. The aim of the study was to assess the changes in the functional and rheological properties of theroad bitumens that were modified by adding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…The benefits of using in hot mix asphalt the Trinidad Epuré (TE) asphalt additives, also referred to in publications as Trinidad Lake Asphalt (TLA), have been scientifically proven. Based on the tests [19,20,21,22] related to the modification of Trinidad Epuré road bitumen additive it was possible to observe a decrease in the penetration value, an increase in the softening temperature value, an increase in resistance to permanent deformations at high temperatures -increase of the G * /sin(δ) parameter. In the case of road pavements made of a hot mix asphalt prepared with the use of an asphalt binder with the Trinidad Epuré additive, an improvement in the workability and compactability of the hot mix asphalt was observed [23].…”
Section: Oil Sandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of using in hot mix asphalt the Trinidad Epuré (TE) asphalt additives, also referred to in publications as Trinidad Lake Asphalt (TLA), have been scientifically proven. Based on the tests [19,20,21,22] related to the modification of Trinidad Epuré road bitumen additive it was possible to observe a decrease in the penetration value, an increase in the softening temperature value, an increase in resistance to permanent deformations at high temperatures -increase of the G * /sin(δ) parameter. In the case of road pavements made of a hot mix asphalt prepared with the use of an asphalt binder with the Trinidad Epuré additive, an improvement in the workability and compactability of the hot mix asphalt was observed [23].…”
Section: Oil Sandsmentioning
confidence: 99%
“…Due to its origins, chemical composition and high molecular mass, Gilsonite is well related to asphalt. Applying this additive for oil-derived asphalt modifications reduces the penetration values and increases the values of softening temperatures of asphalt binders containing Gilsonite [20]. The Gilsonite additive increases resistance to permanent deformations at high temperatures, and also increases the G * /sin(δ) parameter of asphalt binders modified with this additive before and after the ageing process.…”
Section: Asphaltitesmentioning
confidence: 99%
“…In another study, it was found that the storage stability of Gilsonite-modified bitumen was better than SBS modified bitumen [13]. In addition, the results of a study showed that the use of Gilsonite in the appropriate amount had no negative effect on the aging process of bitumen [26]. In many studies it has been reported that HMA modified with Gilsonite had higher stability, lower permanent deformation and better fatigue and moisture resistance [10,13,15,18,23].…”
Section: Introductionmentioning
confidence: 98%
“…Prior to PAV, the samples were subjected to Rolling Thin Film Oven Test (RTFOT) (Słowik & Bilski, 2017). Owing to the addition of the low viscosity modifiers, the temperature of the bituminous mixture production was reduced and the samples were conditioned at 135 °C (instead of conventional 163 °C -by PN-EN 12607-1: Bitumen and bituminous binders.…”
Section: Materials and Test Methodsmentioning
confidence: 99%